(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The biological balance and the fundamental services provided by lakes are crucial to human and environmental well-being, making them valuable resources. But both natural and human caused activities are progressively endangering their quality. In this research, five lakes in the Marathwada area of Maharashtra, India, were analysed for water quality and pollution status using a mix of physico-chemical and GIS approaches. Heavy metals including cadmium, copper, manganese, and nickel, as well as important water quality indicators like hardness, pH, turbidity, chloride, and nitrate were examined. Some metrics, including turbidity and harmful amounts of cadmium, exceeded the allowed limits established by BIS and WHO regulations, indicating substantial contamination in many lakes. Land use and watershed features were analysed spatially using GIS software. This helped pinpoint pollution sources associated with urbanisation, agricultural runoff, and industrial effluents. In order to preserve ecological balance and public health in this semi-arid area that is water-stressed, the results show that targeted pollution control methods, sustainable lake management, and ongoing monitoring are necessary.